Dietary Intake of Vitamin K and Its Association With All-Cause, Cardiovascular Disease and Cancer Mortality in the Danish Diet, Cancer, and Health Cohort. (7th June 2021) - Palmer, Claire; Bellinge, Jamie; Dalgaard, Frederik; Sim, Marc; Murray, Kevin; Connolly, Emma; Blekkenhorst, Lauren; Bondonno, Catherine; Croft, Kevin; Gislason, Gunnar; Tjønneland, Anne; Overvad, Kim; et al.
Abstract: Objectives: Our objective was to examine whether dietary intakes of vitamin K1 and vitamin K2 were associated with all-cause, cardiovascular disease (CVD)-related and cancer-related mortality and to identify subpopulations that may benefit the most from higher vitamin K intakes. Methods: Participants from the Danish Diet, Cancer, and Health Study cohort, between 50–65 years of age at recruitment, completed a food-frequency questionnaire (FFQ) at baseline and were followed up for cancer-related, CVD-related, and all-cause mortality using nationwide registries. Intakes of vitamin K1 (phylloquinone) and vitamin K2 (menaquinones 4–10) were estimated from FFQs, and their relationship with mortality outcomes was determined using Cox proportional hazards models. Results: In total, 56 048 Danish residents, with a median [interquartile range] age of 56 [52–60] years at entry, were followed up for 21 [20–22] years. During follow-up, 14 083 individuals died from any cause; 5015 deaths were CVD-related; and 6342 deaths were cancer-related. Intakes of vitamin K1, but not vitamin K2, were non-linearly inversely associated with both all-cause and cause-specific mortality, after adjusting for demographic and lifestyle confounders. Compared to individuals with the lowest vitamin K1 intakes, individuals with the highest intakes had a 24% [HR (95% CI): 0.76 (0.72, 0.79)] lower risk of all-cause mortality, a 28% [0.72 (0.66, 0.79)] lower risk of CVD-related mortality, and a 20% [0.80 (0.75, 0.86)] lower risk of cancer-related mortality. Furthermore, the association between vitamin K1 intake and cancer mortality appeared to be stronger in smokers than in non-smokers (p for interaction = 0.002). Conclusions: Moderate to high intakes of vitamin K1, but not K2, were associated with a lower risk of all-cause, CVD-related and cancer-related, mortality. Promoting adequate intakes of vitamin K1, particularly in smokers, may help to reduce all-cause, CVD-related and cancer-related mortality at the population level. Funding Sources: The Danish Diet, Cancer, and Health Study was funded by the Danish Cancer Society, Denmark. This study was supported by the Raine Medical Research Foundation and the Healy Medical Research Foundation.